Kepemimpinan Perempuan Perspektif Nurcholis Madjid (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
The emergence of views in some Muslims, especially in Indonesia that places women as weak and inappropriate human beings to participate in the public sphere, because it cannot be separated from those that are still maintained and even maintained, so it seems that it is difficult for women to develop their careers, and even if there are only certain circles and even very limited. However, in Islam, rights and obligations are always the same regardless of human anatomy. Gender does not make a difference in Islam because the concept is justice for anyone and for all. This study uses a library research. A method in colleting data uses library study and documentation. Analyze data uses a descriptive method. Nurcholis Madjid's thoughts on political gender leadership are what will be understood in this study. The results of this study show that there are so many verses that discuss women, while the problems of gender leadership according to Nurcholis Madjid are marginalization, subordination, stereotypes or labeling, violence and the idea that women have a diligent and caring nature, so it is not appropriate to be the head of the house. As a result, women are only responsible for domestic work in the household. As for Nurcholis Madjid's opinion about women's leadership having principles, intellectual traditions, monotheism as the main value, equality and humanity. Keywords: Leadership, Women, Nurcholis Madjid